Uso de regressão linear para estimar parâmetros físico-químicos relacionados à qualidade do jerked beef - Pinto, Marcos Franke [UNESP]; Ponsano, Elisa Helena Giglio [UNESP]; Almeida, Ana Paula da Silva [UNESP]; Perri, Sílvia Helena Ventorulli [UNESP]; Shimokomaki, Massami (My University, 2006)
Jerked beef is officially defined as salted, cured and dried beef. Water activity (Aw), moisture, ash and residual nitrite are the physicochemical parameters that define this product identity and quality standards. In this work, the behavior of these parameters during jerked beef processing was evaluated and a significant correlation among them was revealed. These results allowed the establishment of statistical equations that enable the estimation of all the physicochemical parameters from the results obtained in the measurement of just one of them.
Use of linear regression to estimate physicochemical parameters associated to jerked beef quality
Keywords: Jerked beef; Linear regression; Physicochemical parameters; Quality control